Normalizing Sexuality and the Meaning of the Body: Experiences of Adolescents Engaging in Premarital : Experiences of Adolescents Engaging in Premarital - Lava Nasta Meika; Ahmad Ridwan; Diyah Utami (University of Muhammadiyah Malang, 2026)
Sexuality in adolescence is a social arena that is continuously negotiated through aspects of power, moral rules, and changes in the digital world and social environment. This study aims to examine how sexuality is normalized, how bodies are managed, the process of identity formation, and the negotiation of social and religious values ​​experienced by adolescents, both urban and rural. This study employed a qualitative approach, utilizing in-depth online interviews with adolescent boys and girls aged 18-23. Data were analyzed using Michel Foucault's theoretical framework relating to power and normalization, symbolic interactionism, and the sociology of the body perspective. The research findings reveal that the normalization of adolescent sexuality does not occur through the recognition of formal norms, but rather through social customs, interactions with peers, and repeated digital practices. In urban areas, sexuality tends to be viewed as a private matter, while in rural areas, collective surveillance and social stigma play a significant role in disciplining the body. Adolescent bodies function as a field of power that is negotiated through emotional pressure, self-discipline, and acceptance of moral and religious norms. This study emphasizes that adolescent sexuality is a contextual and multi-layered social process.